Microbial transformation and inhibitory effect assessment of uvaol derivates against LPS and HMGB1 induced NO production in RAW264.7 macrophages. (15th February 2022) - Jiang, Xuewa; Shen, Pingping; Zhou, Jing; Ge, Haixia; Raj, Richa; Wang, Weiwei; Yu, Boyang; Zhang, Jian
Graphical abstract: Microbial transformation of uvaol with Penicilium griseofulvum CICC 40, 293 and Streptomyces griseus ATCC 13, 273 afforded unique regio-selective hydroxylated and intramolecular epoxidized ursane-triterpenes with considerable inhibitory effect on LPS and HMGB1-induced inflammation. Abstract: For the discovery of new pentacyclic triterpenes as a potential anti-inflammatory agent, microbial transformation of uvaol by Penicilium griseofulvum CICC 40293 and Streptomyces griseus ATCC 13273 was investigated. Stereoselective hydroxylation and epoxidation reactions were observed in the biotransformation. Moreover, six new metabolites were isolated and structurally elucidated by HR-ESI-MS and NMR spectrum. All the compounds were evaluated upon the inhibitory effects of nitric oxide (NO) release in RAW 264.7 cells induced by lipopolysaccharide (LPS) and high-mobility group box 1 (HMGB1). Among them, compound 3 (13, 28-epoxy-3 β, 7 β, 21 β -trihydroxy-urs-11-ene) with the unique epoxy structure and compound 5 (3 β, 21 β, 24, 28-tetrahydroxy-urs-12-en-30-oic acid), exhibited a considerable inhibitory effect on both models while compound 2 (urs-12-ene-3 β, 7 β, 21 β, 28-tetraol) showed a significant bias in the LPS-induced inflammatory response with IC50 value of 2.22 μ M. Therefore, this study could provide some insights on the discovery of the pentacyclic triterpene leads for the treatment of either DAMPs or PAMPs triggered inflammation.